(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study aims to apply rhetorical and semantic rules to the "Chapter of Guests" in Abu Tammam’s Ḥamāsah. It focuses on rhetorical structures with different patterns through the relationship between the predicate and the subject, whether in literal or metaphorical predication, as well as the types of information, affirmations, imperative and non-imperative constructions, and the characteristics of sentence components, including: (restriction, omission, and mention). The study discusses the rhetorical purposes carried by these structures. Grammarians have delved deep into poetry and its meanings, as poetry is an aesthetic phenomenon that stems from language, reflecting human genius. Scholars and grammarians have explored the vocabulary and suggestive meanings of poetry to uncover its essence. This study also addresses some grammatical rules, given the high quality of Abu Tammam’s choices in wisdom and eloquence. Abu Tammam was a prominent figure, engaging linguists with his poetry through various studies and research.